Multiferroic Clusters: A New Perspective for Relaxor‐Type Room‐Temperature Multiferroics. (22nd February 2016) - Henrichs, Leonard F.; Cespedes, Oscar; Bennett, James; Landers, Joachim; Salamon, Soma; Heuser, Christian; Hansen, Thomas; Helbig, Tim; Gutfleisch, Oliver; Lupascu, Doru C.; Wende, Heiko; Kleemann, Wolfgang; et al.
Abstract : Multiferroics are promising for sensor and memory applications, but despite all efforts invested in their research no single‐phase material displaying both ferroelectricity and large magnetization at room‐temperature has hitherto been reported. This situation has substantially been improved in the novel relaxor ferroelectric single‐phase (BiFe0.9 Co0.1 O3 )0.4 –(Bi1/2 K1/2 TiO3 )0.6, where polar nanoregions (PNR) transform into static‐PNR as evidenced by piezoresponse force microscopy (PFM) and simultaneously enable congruent multiferroic clusters (MFC) to emerge from inherent strongly magnetic Bi(Fe, Co)O3 rich regions as verified by magnetic force microscopy (MFM) and secondary ion mass spectrometry. The material's exceptionally large Néel temperature T N = 670 ± 10 K, as found by neutron diffraction, is proposed to be a consequence of ferrimagnetic order in MFC. On these MFC, exceptionally large direct and converse magnetoelectric (ME) coupling coefficients, α ≈ 1.0 × 10 −5 s m −1 at room‐temperature, are measured by PFM and MFM, respectively. It is expected that the non‐ergodic relaxor properties which are governed by the Bi1/2 K1/2 TiO3 component to play a vital role in the strong ME coupling, by providing an electrically and mechanically flexible environment to MFC. This new class of non‐ergodic relaxor multiferroics bears great potential for applications. Especially the prospect of a ME nanodot storage device seems appealing. Abstract : Electric field induced magnetoelectric switching of newly discovered multiferroic clusters (MFC) in (BiFe0.9 Co0.1 O3 )0.4 –(Bi1/2 K1/2 TiO3 )0.6 ceramics is reported. Both direct and converse coupling is observed, with the highest reported magnetoelectric coupling coefficient, α ≈ 1.0 × 10 −5 s m −1 ( dE / dH ≈ 1.3 kV (cm Oe)) −1 . It is proposed that MFCs are both ferroelectric and ferrimagnetic. The unusual and robust magnetic properties are emphasized by an extremely high Néel temperature T N = 670 ± 10 K.